2021
DOI: 10.1186/s12889-021-10897-4
|View full text |Cite
|
Sign up to set email alerts
|

Occupational burnout and job satisfaction among physicians in times of COVID-19 crisis: a convergent parallel mixed-method study

Abstract: Background Healthcare professionals including physicians were subjected to an increased workload during the COVID-19 crisis, leaving them exposed to significant physical and psychological distress. Therefore, our present study aimed to (i) assess the prevalence of burnout and levels of job satisfaction among physicians in Jordan, and (ii) explore physicians’ opinions, experiences, and perceptions during the pandemic crisis. Methods This was a mixed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
175
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 198 publications
(203 citation statements)
references
References 63 publications
19
175
0
9
Order By: Relevance
“…These worries might reflect the sense of responsibility among HCWs towards their patients. This finding is congruent with Italian and Jordanian studies which found that most of the physicians and nurses were very anxious about spreading COVID-19 to the people around [12,40]. However, the results showed that worries about dealing with COVID-19 patients diminish with time.…”
Section: • Emotional Reactionssupporting
confidence: 86%
See 3 more Smart Citations
“…These worries might reflect the sense of responsibility among HCWs towards their patients. This finding is congruent with Italian and Jordanian studies which found that most of the physicians and nurses were very anxious about spreading COVID-19 to the people around [12,40]. However, the results showed that worries about dealing with COVID-19 patients diminish with time.…”
Section: • Emotional Reactionssupporting
confidence: 86%
“…Quantitative studies have shown that frontline healthcare providers who treat patients with COVID-19 have greater risks of mental health problems, such as anxiety, depression, insomnia, and stress [11]. Frontline physicians and nurses who had no expertise in dealing with infectious diseases had additional challenges when they shifted into an entirely new work environment [11,12]. The widespread transmission of the virus has intensified challenges in healthcare systems in most countries.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The successive pandemic waves accompanied by many factors such as people's non-compliance to the recommended health precautions, pandemic fatigue, and the pandemic-induced psychologic and economic impacts were all believed to have negative impacts on the epidemic situation in Jordan (9)(10)(11). Also, the successive pandemic waves have impacted the health system imposing a signi cant burden on healthcare institutions and the health workforce in the country (9,12).…”
Section: Introductionmentioning
confidence: 99%